THE ALIENATED SUBJECT IN MODERN SCIENCE AS THE PROBLEM OF HUMANITY - Husain Heriyanto (Khazanah: Jurnal Studi Islam dan Humaniora, 2022)
Those above-mentioned condition in short are not taken it as a given but it is established by the long and pervasive process of secularization of science which is primariy chracterized as the alienated knowing subject in mainstream scientific endeavours.  Such global calamities as injustice, poverty, wars, organized violence, terrorism, arms race, moral disorientation, alienation, abuse of human rights, global warming, and severe damage to nature and environmental sphere are the end-products of complex process of secularization of science.  R.D. Laing says “we have destroyed the world in theory before we destroy it in practice